Ultrasonic pulse induced mechanoluminescence of europium doped strontium aluminate micro-crystals - Sonwane, V D; Gaur, A S; Haldar, B K; Pandey, S; Chandra, B P (Recent Research in Science and Technology, 2012)
When rare earth doped strontium aluminate micro-crystals are exposed to ultrasonic pulse, then mechanumnescence (ML) is induced. The intensity of ML is proportional to the power of ultrasonic pulse used for ML excitation. The ML in europium doped strontium aluminate micro-crystals can be understood on the basis of the piezoelectrically induced electron detrapping model. On the basis of the piezoelectrically-induced electron detrapping model, expressions are derived for the general kinetics of ML intensity, rise of ML intensity, peak ML intensity and decay of ML intensity, in which good agreement is found between the theoretical and experimental results. A linear relation between the ML intensity and the ultrasonic power can also be understood on the basis of the proposed theory. The present investigation shows that the ML can be used to detecting the presence of ultrasonic waves and also for the measurement of ultrasonic power.